Acute sleep restriction increases dietary intake in preschool‐age children. (19th September 2016) - Mullins, Elsa N.; Miller, Alison L.; Cherian, Sherin S.; Lumeng, Julie C.; Wright, Kenneth P.; Kurth, Salome; Lebourgeois, Monique K.
Summary: Epidemiological findings suggest short sleep duration is associated with overweight and obesity across the lifespan. In adults, experimental sleep loss increases caloric intake more than total daily energy needs, thus leading to weight gain. To date, little is known about the relationship between sleep restriction and dietary intake in preschool children. Healthy children ( n  = 10; 41.2 ± 5.4 months; 5 females) followed a strict sleep schedule for 5 days before each experimental condition: 1 day of baseline sleep (nap and scheduled bedtime/wake time) and 1 day of sleep restriction (no‐nap and ~2.3 h bedtime delay). Standardized parent‐report dietary intake measures were obtained on baseline, sleep restriction and sleep recovery ( ad libitum sleep opportunity in the 24‐h following sleep restriction) days. As designed, children slept ~3 h less on the sleep restriction than the baseline day ( P  < 0.001), with no significant differences in sleep between baseline and recovery days (verified with actigraphy). Repeated‐measuresanova s indicated differences across conditions in total kilocalories, sugar, carbohydrate and fat intake (all P  < 0.05; no differences in protein). Post hoc tests revealed that compared with baseline, children consumed 21% more kilocalories, 25% more sugar and 26% more carbohydrates on the day of sleep restriction, as well as 14% more kilocalories and 23% more fat on the day of sleep recovery (all P  < 0.05). Findings suggest that acute sleep loss increases dietary intake in preschoolers both on the day of and the day after sleep restriction. Increased kilocalorie intake may promote weight gain over time and be a mechanism through which short sleep contributes to childhood obesity risk.